2014
DOI: 10.3329/bmj.v40i2.18498
|View full text |Cite
|
Sign up to set email alerts
|

Response of Reporting Adverse Drug Reactions among Medical Practitioners

Abstract: Adverse drug Reactions (ADRs) is a global problem of major health concern. Spontaneous reporting of ADRs is the cornerstone of pharmacovigilance. However, underreporting is a huge problem due to lack of reporting culture among medical practitioners. This observational descriptive study was done with the aim to find out the response of reporting adverse drug reactions among medical practitioners and to describe pattern of adverse drug reactions during their practice. Self administered ADR reporting form was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…In this study, the response rate (70%) was higher than that observed in similar studies performed by Khan et al (63%), Fadare et al (59%), Nahar et al (34%), and Alshakka et al (18%) in India, Nigeria, Bangladesh and Malaysia, respectively (Alshakka et al, 2013, Fadare et al, 2011, Khan et al, 2013, Nahar et al, 2011). However, studies conducted in Nepal and Nigeria had better response rates of 74% and 82%, respectively (Oshikoya and Awobusuyi, 2009, Santosh et al, 2013).…”
Section: Discussioncontrasting
confidence: 68%
“…In this study, the response rate (70%) was higher than that observed in similar studies performed by Khan et al (63%), Fadare et al (59%), Nahar et al (34%), and Alshakka et al (18%) in India, Nigeria, Bangladesh and Malaysia, respectively (Alshakka et al, 2013, Fadare et al, 2011, Khan et al, 2013, Nahar et al, 2011). However, studies conducted in Nepal and Nigeria had better response rates of 74% and 82%, respectively (Oshikoya and Awobusuyi, 2009, Santosh et al, 2013).…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies have shown that not all ADRs are reported, and most of these studies have recommended the adoption of spontaneous reporting and the provision of education to healthcare workers about the ADR reporting process. 12 In addition, one of the recent advances in the field of pharmacy is that in developed countries pharmacists are increasingly being given a more clinically active role to ensure patient safety and the effective use of medicines. One aspect of this expansion of the pharmacists' role is that they are given the authority to report ADRs in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted from December 2009 to December 2010 to find out response of reportingADRs in one teaching hospital and 10 private chambers revealed that response of reporting of ADR from private chamber was very poor (29%) whereas response from teaching hospital was more (55%) (Nahar et al, 2011) …”
Section: Necessity Of Pharmacovigilance Study In Bangladeshmentioning
confidence: 99%